Two Pools of Epoxyeicosatrienoic Acids in Humans: Alterations in Salt-Sensitive Normotensive Subjects - Elijovich, Fernando; Milne, Ginger L; Brown, Nancy J; Laniado-Schwartzman, Michal; Laffer, Cheryl L (Hypertension (Dallas, Tex. 1979), 2018)
We measured epoxyeicosatrienoic acids (EETs) and dihydroxyeicosatrienoic acids (DHETs) in 21 normotensive subjects classified as salt resistant (13) or salt sensitive (8) with an inpatient protocol of salt loading (460 mEq Na /24 hours, HiNa) and depletion (10 mEq Na /24 hours+furosemide 40 mg×3, LoNa). No urine EETs were detected; hence, enzyme linked innumosorbent assay 14,15-DHETs (dihydroxyeicosatrienoic acids) were considered the total converted 14,15-urine pool. We report ultra-performance liquid chromatography/tandem mass spectrometry plasma EETs, DHETs, and their sum (plasma total pool) for the 3 regioisomers (8,9-, 11,12-, 14,15-) and their sum (08,15-). In salt-resistant subjects, urine total pool was unchanged by HiNa, decreased by LoNa, and correlated with urine sodium excretion, fractional excretion of Na , and Na /K ratio for the 3 days of the experiment combined ( <0.03). In contrast, plasma total pool increased in LoNa and did not correlate with natriuresis or Na /K ratio but showed correlations between EETs, blood pressures, and catecholamines and between DHETs and aldosterone ( <0.03). Urine total pool of salt-sensitive was lower than that of salt-resistant subjects in certain phases of the experiment, lacked responses to changes in salt balance, and exhibited limited correlations with natriuresis and Na /K ratio during LoNa only. Plasma total pool of salt-sensitive was lower than in salt-resistant subjects and did not correlate with blood pressures or aldosterone but did with catecholamines. We conclude that the urine total pool reflects a renal pool involved in regulation of natriuresis, whereas the plasma total pools are of systemic origin, uninvolved in Na excretion, perhaps contributing to regulation of vascular tone. Data suggest that abnormalities in EETs in salt-sensitive subjects participate in their renal or vascular dysfunction, which has potential therapeutic implications.